Development of a "cooling" menthol energy gel for endurance athletes: effect of menthol concentration on acceptability and preferences - Stevens, C. J.; Ross, M. L.; Vogel, R. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Menthol is effective at stimulating thermosensitive neurons that evoke pleasant cooling sensations. Internal application of menthol can be ergogenic for athletes, and hence, addition of menthol to sports nutrition products may be beneficial for athletes. The aim of this study was to develop a menthol energy gel for consumption during exercise and to determine acceptability and preferences for gels with different menthol concentrations. With a randomized, crossover, and double-blind placebo-controlled design, 40 endurance athletes (20 females) ingested an energy gel with a menthol additive at a high (0.5%; HIGH) or low concentration (0.1%; LOW), or a mint-flavored placebo (CON), on separate occasions during outdoor endurance training sessions. The athletes rated the gels for cooling sensation, mint flavor intensity, sweetness, and overall experience and provided feedback. Results are reported as median (interquartile range). Both menthol gels successfully delivered a cooling sensation, with a significantly greater response for HIGH (5.0 [4.0-5.0]) compared with LOW (3.5 [3.0-4.0]; p = .022) and CON (1.0 [1.0-2.0]; p < .0005), and LOW compared with CON (p < .0005). Ratings of mint flavor intensity followed the same trend as cooling sensation, while ratings of overall experience were significantly worse for HIGH (2.0 [1.0-3.0]) compared with LOW (4.0 [2.0-4.0]; p = .001) and CON (4.0 [3.0-4.0]; p < .0005). An energy gel with the addition of menthol at 0.1-0.5% provides a cooling sensation for athletes with a dose-response when ingested during exercise. The 0.1% concentration is recommended to maximize the overall experience of the gel.